Partisipasi Stakeholder Dalam Pelestarian Kawasan Rindam IV / Diponegoro Kota Magelang Sebagai Kawasan Bersejarah - Kurniawan, Nanang (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
A well preserved heritage site may provide an identity to a city, distinguishing it from the others, however, its preservation efforts often face difficulties because they collide with other activities aimed at economic growth. RINDAM IV/Diponegoro area in Magelang City, Central Java is an example of such circumstance. The area is basically an active defense headquarters and military academy located in a city with a long national military history. The study examines the participation of stakeholders namely the Indonesian ARMY (TNI-AD) and Magelang City government in the conservation of RINDAM IV/Diponegoro area in Magelang, through quantitative approach using frequency distribution analysis. Analysis indicated a large amount of support from stakeholders, concerning the conservation of RINDAM IV/Diponegoro area as a heritage site by implementing eight asset management efforts. Each stakeholder provides contribution varyingÂ  according to its authority and capacity. The study found indications of well established coordination between the ARMY and the City Government. However, a better synergy involving the ARMY, City Government, managers and users of the heritage site, analysts and the community is needed to support conservation efforts which is sustainable and can benefit the future generations.